On Christian nationalism: critical and theological perspectives - Gides, David M.; Braune, Joan (Routledge studies in fascism and the far right, 2026)
"Since the January 6, 2021 coup attempt at the U.S. Capitol, Christian nationalism has widely been called the "greatest threat to democracy in the United States." Yet academics and activists present many conflicting definitions and solutions. On Christian Nationalism: Critical and Theological Perspectives features an array of scholarly essays on Christian nationalism, offering innovative exploration of topics including: definitions and historical context, current trends in the United States (including intersections with racism, sexism, antisemitism and Islamophobia), comparative phenomena abroad, and practical ways to address the problem theologically or politically. An important book at a time of rising Christian far-right mobilization and urgent need for a deeper theoretical analysis, On Christian Nationalism pushes the conversation further and explores new vantage points. The book will be of interest to those seeking a fuller, richer, and more complex understanding of Christian nationalism, including scholars of religious and political movements, as well as others (activists, pastors, journalists) with a concerned focus in the area"-- Provided by publisher